[How frequent are poor prognostic markers in rheumatoid arthritis? : An estimate based on three epidemiologic cohorts] - Albrecht, K.; Richter, Adrian; Meißner, Yvette; Huscher, D.; Baganz, L.; Thiele, Katja; Schneider, M.; Strangfeld, A.; Zink, A. (Z Rheumatol, 2017)
BACKGROUND: Unfavorable prognostic factors-high disease activity, early erosions, and autoantibodies-should be considered when making treatment decisions in rheumatoid arthritis (RA). There are little data on the frequency of individual poor prognostic factors among RA patients in daily care. METHODS: Disease activity (Disease Activity Score, DAS28), erosions, antibodies against citrullinated peptides or rheumatoid factor (ACPA/RF+), previous treatment failure, inflammation markers, and functional disability (FFbH < 70) were defined as prognostic factors. Different treatment decision making situations were evaluated in disease-modifying antirheumatic drug (DMARD)-naive patients from the early RA CAPEA cohort (n = 1059), and in patients from the biologics register RABBIT after failure of one (n = 2217) or more (n = 3280) conventional synthetic (cs)DMARDs or one (n = 1134) or more (n = 795) biologic (b)DMARDs. With the national database of German arthritis centers (NDB), the frequency of these factors was analyzed according to treatment strata (no/1(st)/2(nd)/3(rd) DMARD; n = 5707). RESULTS: In DMARD-naive patients (CAPEA), 50% presented with DAS28 > 5.1, 64% were ACPA/RF+, 13% had erosions, and 37% functional disability (FFbH < 70). In RABBIT, 63 (1(st) csDMARD failure) to 81% (>/=2 bDMARD failures) were ACPA/RF+, 29 to 70% had erosions, 33 to 52% DAS28 > 5.1, and 41 to 66% had FFbH < 70, respectively. In the NDB, between 47 (DMARD-naive) and 82% (>/=2 previous DMARDs) were ACPA/RF+, 5 to 11%, had high disease activity under treatment (DAS28 > 5.1), and 26 to 50% had functional disability (FFbH < 70), respectively. CONCLUSION: With growing numbers of previous DMARD therapies, increasing proportions of patients have poor prognostic factors. This underlines the importance of these factors for a difficult-to-treat disease course.